Pilot study protocol to inform a future longitudinal study of ageing using linked administrative data: Healthy AGeing in Scotland (HAGIS). Issue 1 (10th January 2018) - Douglas, Elaine; Rutherford, Alasdair; Bell, David
Abstract : Introduction: Population ageing is a welcome testament to improvements in the social, economic and health circumstances over the life course. However, these successes necessitate that we understand more about the pathways of ageing to plan and cost our health and social care services, to support our ageing population to live healthier for longer and to make adequate provisions for retirement. Longitudinal studies of ageing facilitate such understanding in many countries around the world. Scotland presently does not have a longitudinal study of ageing, despite dramatic increases to its ageing population and its poor health record. Healthy AGeing in Scotland (HAGIS) constitutes the launch of Scotland's first comprehensive longitudinal study of ageing. Methods: A sample of 1000 people aged 50+ years will be invited to take part in a household social survey. The innovative sampling procedure used administrative data to identify eligible households. Anonymised survey responses will be linked to administrative data. Ethics and dissemination: Ethics approval was obtained from the host institution for the study design and from the Public Benefits and Privacy Panel for administrative data linkage. Anonymised survey data will be deposited with the UK Data Service. A subset of survey data, harmonised with other global ageing studies, will be available via the Gateway to Global Aging platform. These data will enable powerful cross-country comparisons across the social, economic and health domains that will be relevant for national and international research. Research publications from the HAGIS team will be disseminated through journal articles and national and international conferences. The findings will support current and future research and policy debate on ageing populations.